A relação entre o desempenho do estoque e o desempenho financeiro na indústria brasileira entre os anos de 2004 e 2014 - Perressim, William Sbrama (2016)
The efficiency of a production system is characterized by its ability to produce more with fewer resources. In this sense new strategies for inventory management emerge, to minimize the impact of this factor in the results of the organizations. Literature in operations management deals with a long time to study and analyze the relationship between the stock of the economic and financial performance. But even in the face of decades of research, some issues show up unanswered. In this sense this work is to analyze the influence of the stock's performance on the economic and financial results, making use of indicators based on Gross Profit, Operating Income and Net Income, analyzing the relationship between the composition of these indicators and their effectiveness in isolating the effect of stock on economic and financial performance. For such a set of 56 industries with publicly traded and listed on the BM&FBovespa, were analyzed their data financial performance and operational arranged in the form of panel, with the start in the 1st quarter of 2004 and finish in the 4th quarter 2014 total so 11 years and 2376 observations. Regression analysis with panel data using the model of generalized least squares indicated that the economic and financial performance is positively impacted by stock, that is, reductions in inventory levels should impact in better profits for the organization. also indicated the ROABruto (Gross Profit) and BEP (Operating Income) show to be more influenced by the stock compared to indicators based on net income.